2008
DOI: 10.1590/s1415-47572008000300029
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of Bemisia tabaci biotypes: RAPD, PCR-RFLP and sequencing of the ITS1 rDNA region

Abstract: The Bemisia tabaci complex is formed by approximately 41 biotypes, two of which (B and BR) occur in Brazil. In this work we aimed at obtaining genetic markers to assess the genetic diversity of the different biotypes. In order to do that we analyzed Bemisia tabaci biotypes B, BR, Q and Cassava using molecular techniques including RAPD, PCR-RFLP and sequencing of the ITS1 rDNA region. The analyses revealed a high similarity between the individuals of the B and Q biotypes, which could be distinguished from the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Beside these biotype another were detected under Brazilian condition: biotype A or subsequently referred to as biotype BR by (Lima et al 2000). The Q biotype has not yet been reported from Brazil (Rabello et al, 2008) and represents a threat due to its resistance to pyriproxyfen (Horowitz et al, 2003), buprofezin and reduced susceptibility to the neonicotinoid insecticides imidacloprid, acetamiprid and thimethoxam (Hodges, 2009), currently used to control B. tabaci.…”
Section: Introductionmentioning
confidence: 99%
“…Beside these biotype another were detected under Brazilian condition: biotype A or subsequently referred to as biotype BR by (Lima et al 2000). The Q biotype has not yet been reported from Brazil (Rabello et al, 2008) and represents a threat due to its resistance to pyriproxyfen (Horowitz et al, 2003), buprofezin and reduced susceptibility to the neonicotinoid insecticides imidacloprid, acetamiprid and thimethoxam (Hodges, 2009), currently used to control B. tabaci.…”
Section: Introductionmentioning
confidence: 99%
“…There are probably common annealing sites, present in the genomes of both biotypes, indicating the cross-amplification of the Scar marker developed to detect the B biotype of B. tabaci. Rabello et al (2008) analyzed a 550-bp fragment related to the amplification of the ITS1 rDNA of the B and Q biotypes, which was digested by the AvaI, DdeI, and Sau3A restriction enzymes. These authors established a dendrogram, which showed 100% genetic similarity between both biotypes.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the presence of two biotypes has been detected: one native (BR) and one introduced, known as biotype B (Rabello et al, 2008). The BR biotype is not very well studied (Alemandri et al, 2012), but the B biotype has been reported for its extensive list of host plants and high potential for virus transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In other groups, RAPD Genetic variability in Steindachneridion melanodermatum markers have been combined with methodologies of a less arbitrary nature in order to generate better defined DNA patterns, i.e., DNA fingerprinting, for the purpose of molecular characterization (Aggarwal et al, 2008;Demir et al, 2010), for analysis of genetic diversity (Brahmane et al, 2008;Rabello et al, 2008) to provide practical information for selection of parentals in planning breeding strategies (Ahmad et al, 2010), and to determine phylogenetic relationships (Marouelli et al, 2010) besides population differentiation (Klinbunga et al, 2010) between wild and cultivated stocks (Sesli and Yegenoglu, 2010). Although the RAPD method does not provide accurate information regarding the specific genotype of the specimens analyzed or the dominant character of the marker, it is a fast, inexpensive tool that allows access to information on general genetic variability within and between populations, even when considering that the observed variation may be underestimated.…”
Section: Discussionmentioning
confidence: 99%